PENGARUH PEMBERIAN SENAM HIPERTENSI TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Faradina Aprillia; Ikhsan Kamil; Zahra Maulidia Septimar (Nusantara Hasana Journal, 2022)
Hypertension is a common public health problem in developing countries. Hypertension exercise is one of the sports that aims to increase blood flow and oxygen supply in the blood of active muscles and skeleton, one of which is the heart muscle. Objective: To determine the effect of hypertension exercise on reducing blood pressure in patients with hypertension in Rt.003/Rw.001 Kec. Cikupa District. Tangerang Banten in 2022. Research Methods: Using a research design One-Group Pretest-Posttest Design. Where this design is to determine the respondent's blood pressure at the beginning before giving the intervention. So that researchers will find out whether there is a difference before giving the intervention with after the intervention on the response. The sample that I will examine is 14 respondents. The intervention was carried out for 15 minutes with 8 meetings in 2 weeks. Blood pressure was analyzed using the Wilcoxon Signed Ranks Test. Results: from a total of 14 respondents, the results obtained were male and female as many as 7 respondents with a percentage (46.7%). Measurement of blood pressure before the hypertension exercise intervention above showed results for the category of hypertension level 2 as many as 8 respondents (53.3%), for the category of hypertension level 1 as many as 3 respondents (20.0%), and for the category of PreHypertension as many as 3 respondents (20.0%). Measurement of blood pressure again after the hypertension exercise intervention obtained blood pressure with level 1 hypertension category as many as 9 respondents (60.0%), and blood pressure included in the PreHypertension category as many as 5 respondents (33.3%). From a total of 14 respondents, it was found that the p value was 0.000, meaning (p <α = 0.05). That it can be concluded "there is an effect of hypertension exercise on reducing blood pressure in patients with hypertension in Rt.003B/001 Bunder Village, Cikupa District, Tangerang Regency"